Welcome from the International Society of Biomechanics - Wartenweiler, J. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
I bring you the greetings of the International Society of Biomechanics, and I sincerely wish you a successful meeting. You have assembled here to present your papers, report on your research findings, and discuss practical problems in biomechanics of swimming. It will be possible for those who participated in the first symposium 4 years ago to compare it with this meeting. Formerly the main topic was the analysis of various movements in swimming; measurements of the resistance of the water with different positions of the body; and measurements of force when swimming, taking off, and diving. Furthermore, experiments were shown, theories discussed, and models demonstrated as an explanation of the pushing power by arms and legs. Many of these studies were somewhat unsophisticated. The developments that have occurred in the interim will be readily apparent. The fact that so many of you are present today is proof that more scientific information is needed on swimming, diving, and water polo. The necessity of sharing information justifies the efforts the president of this symposium, Leon Lewillie, and his general secretary, Jan P. Clarys, have put forth in organizing this second symposium.